The Effect of Fiber Length on the Strength of Composites as Boat Body Materials - Anggun Pratika; Yuliyanto Yuliyanto; Juanda Juanda (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study investigates the effect of coconut fiber length on the mechanical performance of polyester-based composite materials intended as an alternative body material for small boats, addressing the growing demand for sustainable and locally sourced marine materials. Methodology: An experimental research design was employed using coconut fiber reinforcements with lengths of 10 mm, 30 mm, and 50 mm at a fixed fiber–resin ratio of 5%:95%. Composite specimens were fabricated using the hand lay-up method, reflecting practical production conditions commonly used in small-boat construction. Mechanical characterization was conducted using flexural strength testing in accordance with ASTM D790-02 and impact strength testing in accordance with ASTM E-23, using a Zwick Roell Z020 universal testing machine. Main Findings: The results demonstrate a clear positive correlation between fiber length and mechanical strength, with longer fibers providing more effective stress transfer and energy absorption within the composite matrix. The composite reinforced with 50 mm of coconut fiber exhibited the highest performance, achieving a flexural strength of 63.4 MPa and an impact strength of 45.42 kJ/m², both of which meet the mechanical requirements for small-boat materials set by the Indonesian Classification Bureau. Novelty/Originality of this study: Optimization of coconut fiber length for marine-grade polyester composites, offering empirical evidence that locally available natural fibers can meet regulatory standards for small vessel applications. This research advances eco-friendly composite technology and presents coconut fiber–reinforced polyester as a viable, sustainable alternative to conventional wood-based boat materials.